Immediate results of reconstructive interventions depending on functional types of mitral regurgitation - O. Luchynets (Ukrainian Journal of Cardiovascular Surgery, 2017)
The study is based on analysis of clinical data 218 patients with mitral valve who were treated in the surgical control in The National Amosov Institute of Cardiovascular Surgery of Ukraine from the period 01.01.2010 to 01.01.2015 years. The average age of patients was 52,8±13,0 years. Stereotypes of the surgical reconstruction mitral valve (MV) were based on the leading mechanism of regurgitation matching three functional types for A.Carpantier.The approach to surgical reconstruction MV based on the leading mechanism of regurgitation. The first functional type included 19 (8.7%) patients. This group included the fewest cases of acute heart failure (AHF) in the postoperative period – 3 (15.8%) and hospital mortality was – 1 (5.3%) cases. The second type of functional mitral regurgitation included 174 (79.8%) patients. Patients in this group had the lowest hospital mortality – 2 (1.2%) cases. The third type of functional mitral regurgitation included 25 (11.5%) patients with secondary mitral insufficiency. This group included almost half of 12 (48.0%) cases, signs of AHF in the postoperative period, mortality was 2 (8.0%) cases.